The political domination over procreation - Schooyans, Michel (Medicina e Morale, 1993)
After an historical introduction about the relationship between politics and medical-biological disciplines, the Author points out two forms of political interference with procreation, of which the first is discreet and the second is manifest. The former is the work of "private individuals" with the tacit guarantee of the political authorities; the latter is formulated and set up by a direct mandate of the public powers. What is the result of this? Man is reduced to an "object" that can be manoeuvered and for whom decisions can also be made. It's enough to think of the numerous campaigns for demographic control, even carried out in a compulsory manner. According to the Author, the answer to what is happening and the strength to overcome these intolerable situations, can be found by recuperating the awareness that man is God's creature and should be respected as such.